Fostering Resilience: An In-depth Investigation into the Dynamics of Growth and Development in Slum Children - Hossan, Md. Alomgir (MultiTech Publisher, 2024)
The goal of the study is to understand the socio-economic and educational circumstances of Slum dwellers in the Rajshahi City Corporation. The study was carried out in the Jahaj Ghat area, which is located on the Padma River. 31 street children were chosen to collect data at random from the vulnerable slum. Interviews and questionnaires were conducted with the kids and their family heads. The finding reveals that the households are at significant risk related to housing, shelter, sanitation, water, social security, education, health, and livelihood troubles. Finally, the study recommended resolving the existing problems which will empower the parents of the slum dwellers to provide adequate support for their children to continue schooling.